Equity, Access to Health Care Services and Expenditures on Health in Nicaragua - Angel-Urdinola, Diego; Cortez, Rafael; Tanabe, Kimie (World Bank, Washington, DC, 2013)
Nicaragua has embarked on an ambitious health sector program, which has contributed to significant progress in the health sector over the past decade. Health indicators show gradual but steady improvements: access to basic services such as clean water and sanitation facilities has improved, as have other related performance indicators such as life expectancy, infant/child mortality, immunization rates, and child nutrition among others. Despite these achievements, there are still large inequities in access and quality of health services across socioeconomic groups and regions. Poor individuals living in rural areas (especially in the Central and Atlantic regions), the indigenous population, and individuals living in households engaged in agriculture have average access to health care services and preventive care. The lack of risk mitigation mechanisms such as insurance and social security is causing users in Nicaragua to spend, out-of-pocket, a significant share of their income on health care, especially to buy medications and other non-consultation items such as medical tests. Long distances, lack of medicines, and high costs and other demand-side factors (such as self-prescription) constitute the main constraints causing poor and sick individuals to seek informal care or not to seek care at all.